2003
DOI: 10.1093/toxsci/kfg151
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methylmercury on Midbrain Cell Proliferation during Organogenesis: Potential Cross-Species Differences and Implications for Risk Assessment

Abstract: 5'-bromodeoxyuridine (BrdU) labeling was employed to explore the effects of methylmercury (MeHg) on cell cycle kinetics in the developing rat midbrain during gestational days (GDs) 11 to 14. Contrary to what has been previously reported in mice, no effects of MeHg on cell cycle kinetics were observed up to embryonic brain concentrations of 3-4 microg/g. The absence of an effect was confirmed using stereology and counts of midbrain cell number. Treatment with colchicine, the positive control, resulted in signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 39 publications
4
27
0
Order By: Relevance
“…In vivo studies revealed that a maternal hair concentration of 4.5 ppm MeHgCl as the lowest observed adverse effect level (LOAEL) found in the literature results in neuropsychological deficits in children (Castoldi et al 2001). According to toxicokinetic calculations (Burbacher et al 1990;Lewandowski et al 2003), this hair concentration should resemble an infant brain concentration of approximately 72 nM. In rats, prenatal low-dose administrations of 0.01 mg/kg MeHgCl from gestational day (GD) 6 to 9, which are estimated to result in maximal fetal brain concentrations of 30 nM (Burbacher et al 1990;Lewandowski et al 2003), affected learning behavior in the progeny (Bornhausen et al 1980).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies revealed that a maternal hair concentration of 4.5 ppm MeHgCl as the lowest observed adverse effect level (LOAEL) found in the literature results in neuropsychological deficits in children (Castoldi et al 2001). According to toxicokinetic calculations (Burbacher et al 1990;Lewandowski et al 2003), this hair concentration should resemble an infant brain concentration of approximately 72 nM. In rats, prenatal low-dose administrations of 0.01 mg/kg MeHgCl from gestational day (GD) 6 to 9, which are estimated to result in maximal fetal brain concentrations of 30 nM (Burbacher et al 1990;Lewandowski et al 2003), affected learning behavior in the progeny (Bornhausen et al 1980).…”
Section: Discussionmentioning
confidence: 99%
“…A recent article by Lewandowski et al (2003) compared in vivo and in vitro effects of MeHg on cell cycling and proliferation. To permit these comparisons, a common dose metric (g Hg/gm cellular material) was developed that allowed for comparison of tissue concentrations in order to relate these to MeHg toxicity observed in in vitro and in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, few studies have investigated the accumulation and effect of mercury in the nervous system at < 24h (Harry et al, 2004). In recent work by Lewandowski et al (2003), comparable brain mercury concentrations (~1-3μg/g) did not alter cell cycle kinetics in embryonic rat midbrain. Our results indicate that region-specific responsiveness is an important aspect of mercury toxicity, potentially accounting for these differences.…”
Section: Mehg Has Rapid Differential Effects On Proliferation In Devmentioning
confidence: 95%
“…Similarly, while midbrain cells are resistant to MeHg exposure in vivo (Lewandowski et al, 2003), they show cell cycle alterations in culture (Ponce et al, 1994). The inconsistency between in vitro and in vivo responses may represent a deficiency in cell culture models, differences on Hg levels to which cells are exposed, or the presence of protective factors in vivo.…”
Section: Mehg Has Rapid Differential Effects On Proliferation In Devmentioning
confidence: 99%